2022
DOI: 10.1128/spectrum.02495-21
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Immune Responses to Vector, Mix-and-Match, or mRNA Vaccines against SARS-CoV-2 and the Relationship between the Two Immune Responses

Abstract: There have been few studies that comprehensively evaluated factors affecting immune responses and the correlation between humoral and cellular immune responses after vector, mix-and-match, and mRNA vaccines against SARS-CoV-2. Therefore, we analyzed the effects of age, sex, and the different vaccine regimens on the immune responses to vaccination against SARS-CoV-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…sVNT is a commercially available assay and showed a good correlation with the gold-standard method and the nAb titer [9,27]. However, the TA values and correlation results were very different depending on the RBD assay platform, the number of vaccinations, and vaccine type [4,5]. In this study, the RBD Ab assays and nAb assay showed moderate to strong agreement (kappa 0.76-0.83), and correlation coe cients were strong to very strong (ρ = 0.88-0.94).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sVNT is a commercially available assay and showed a good correlation with the gold-standard method and the nAb titer [9,27]. However, the TA values and correlation results were very different depending on the RBD assay platform, the number of vaccinations, and vaccine type [4,5]. In this study, the RBD Ab assays and nAb assay showed moderate to strong agreement (kappa 0.76-0.83), and correlation coe cients were strong to very strong (ρ = 0.88-0.94).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is the safest and most effective tool to control the pandemic. The population acquires humoral or cellular immune responses against SARS-CoV-2 through vaccination [2][3][4]. The immune response can be assessed by several tests including SARS-CoV-2 antibody binding assay (Ab assay), SARS-CoV-2 neutralizing antibody assay (nAb assay), and interferon-gamma release assay (IGR assay) (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be analyzed in more detail whether or not these sex-specific differences in the immune response to SARS-CoV-2 infection or vaccination may be also important to understand better our key findings. Sex-dependent effects of either infection or vaccination with regard to the humoral and cellular responses have been reported [ 25 ]. Sex can affect the innate and adaptive immune system responses, predisposition to autoimmunity, and vaccine efficacy [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the study written by Nan et al (2022) whose title is Humoral and Cellular Immune Responses to Vector, Mix-and-Match, or mRNA Vaccines against SARS-CoV-2 and the Relationship between the Two Immune Responses, there were differences in immune response induced after mix-match vaccination depending on sex or age of each individual. According to this article, the mixed match of mRNA vaccine induced a robust immune response [38].…”
Section: Written By Myself (2019) Whose Title Is Shoulder and Elbow T...mentioning
confidence: 99%
“…In case report five, he used CoronaVac, Pfizer, and Astra-Zeneca. All articles that we have in the literature are studying the propensity of cancer patients to acquire COVID-19 and the necessity of vaccinating this group of patients [38].…”
Section: Written By Myself (2019) Whose Title Is Shoulder and Elbow T...mentioning
confidence: 99%